2007
DOI: 10.1016/j.cell.2007.03.017
|View full text |Cite
|
Sign up to set email alerts
|

The BH3-Only Protein Bid Is Dispensable for DNA Damage- and Replicative Stress-Induced Apoptosis or Cell-Cycle Arrest

Abstract: Bid, a caspase-activated proapoptotic BH3-only protein, is essential for Fas-induced hepatocyte destruction. Recent studies published in Cell produced conflicting results, indicating that loss of Bid either protects or enhances apoptosis induced by DNA damage or replicative stress. To resolve this controversy, we generated novel Bid-deficient mice on an inbred C57BL/6 background and removed the drug-selection cassette from the targeted locus. Nine distinct cell types from these Bid-deficient mice underwent cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
186
7
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 189 publications
(201 citation statements)
references
References 35 publications
6
186
7
1
Order By: Relevance
“…Importantly, it has been shown that Bid is essential for CD95-induced apoptosis in hepatocytes but dispensable in thymocytes. 22,23 This indicates that CD95-mediated signaling in thymocytes can be considered as Type I, while hepatocytes can be classified as Type II cells. In addition, an important role of XIAP in the amplification of Type I signal has been reported recently.…”
Section: Cd95mentioning
confidence: 99%
“…Importantly, it has been shown that Bid is essential for CD95-induced apoptosis in hepatocytes but dispensable in thymocytes. 22,23 This indicates that CD95-mediated signaling in thymocytes can be considered as Type I, while hepatocytes can be classified as Type II cells. In addition, an important role of XIAP in the amplification of Type I signal has been reported recently.…”
Section: Cd95mentioning
confidence: 99%
“…Curiously, this dependence on Bid for amplification of the cell death signal has been shown to be necessary in some cell types, such as hepatocytes 195,196 , but not in others 197 .…”
Section: The Extrinsic Pathwaymentioning
confidence: 99%
“…To exclude potential off-target effects of bim siRNA in the protection against excitotoxic apoptosis, we availed of a panel of gene-targeted mice deficient for various BH3-only proteins (Bouillet et al, 1999;Villunger et al, 2003;Kaufmann et al, 2007). Neocortical neurons were exposed to 100 µM NMDA for 5 min, as NMDA receptors predominantly mediate glutamate excitotoxicity in cortical neurons .…”
Section: Bim Mediates Excitotoxic Apoptosismentioning
confidence: 99%